From Zeno to arbitrage essays on quantity, coherence, and induction - Skyrms, Brian (Oxford : Oxford University Press, 2013)
Brian Skyrms presents a set of influential essays which deploy formal methods to address epistemological and metaphysical questions. The first part of the book focuses on quantity; the second on degrees of belief, belief revision, and coherence; the third on aspects of inductive reasoning.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Knowledge, Theory of; Metaphysics; Quantity (Philosophy); Sense of coherence; Induction (Logic)